FUZZY LOGIC CONTROL OF AIR-CONDITIONING SYSTEM IN LECTURER ROOM OF STMIK INDONESIA PADANG - Gusrino Yanto (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2017)
Abstract. The research on Fuzzy logic control of air-conditioning system in lecturer room of STMIK Indonesia Padang has been done. AC is a system or machine designed to stabilize the air temperature and humidity of an area used for cooling or heating depending on the nature of air at certain time. Commonly the AC uses a refrigeration cycle but sometimes uses evaporation. Lecturer room of STMIK Indonesia Padang has a size of 120 m2 and consists of 32 rooms. For the convenience of lecturers activity, the room is equipped by three AC each of 3 PK. The room has problems in determining the right size in the AC setting, sometimes the air temperature in the room is too cold or too hot. There are many activities conducted in the lecturer room, in the form of providing excellent service to students, such as thesis supervision, practical work, and discussion activities. With the number of lecturers in the room that is as many as 32 people and each serves about five to ten students daily then the room temperature sometimes becomes unstable. Based on the results of the study, with the room size of 120 m2 and the number of person as many as 100 people using three AC (each with 3 PK capacity) so the appropriate temperature is at position 18.0 ºC.Keywords: Air Conditioner, Fuzzy Logic, and Temperature